The relative effect of structural forms on the ionizing constituents of acids derived from benzoyl acetone and dimedome at different temperatures - Fidaa Hasan Marei; Adil Saeed Azzouz (College of Education for Pure Sciences, 2010)
Abstract The project deals with the determination of ionization constants Ka for ten acidic compounds whose nomenclatures and structures are seen in the text, derived from benzoyl acetone and dimedone by using conductivity method. These compounds are in forms of monoxime, dioxime and phenolic Schiff bases having phenolic groups in ortho, meta and para positions on the aromatic rings. The relative values of ionization constants Kr are calculated in water for the three systems mentioned at five different temperatures and showed a different relationships. The thermodynamic parameters of ionization for acids are also estimated. This shows that the process of ionization of acidic compounds under study in water solvent is non spontaneous (+ΔG), endothermic (+ΔH) and is accompanied by an increase of order (-ΔS) for the ionization systems. Finally a suitable interpretations for any one of these thermodynamic parameters are given and discussed.